The Origins of Energy and Environmental Policy in Europe : the Beginnings of a European Environmental Conscience. - Hoerber, Thomas C. (Routledge research in environmental politics., 2012)
This book examines the development of a European environmental conscience through successive steps of European integration in energy policy. In the 1960s-70s, the world was slowly beginning to realise that environment degradation was not sustainable. With phenomena such as acid rain, it became clear that pollution did not stop at national boundaries and the European environmental conscience developed in parallel to such growing environmental concerns. The oil crisis in 1973 was a turning point in the integration process for both energy policy and environment policy, and while.